Multicolour optical variability monitoring of blazars with high time resolution. Issue 3 (7th February 2023) - Chang, X; Yi, T F; Xiong, D R; Liu, C X; Yang, X; Li, H Z; Gong, Y L; Na, W W; Li, Y; Chen, Z H; Chen, J P; Mao, L S
ABSTRACT: We carried out a high time-resolution, multicolour optical observing campaign for eight gamma-ray detected blazars during 2010–2020. We analyse flux variations, correlations between magnitudes and colours on different time-scales. Intraday variability is detected in all eight sources of our sample. A bluer-when-brighter (BWB) chromatic trend is dominant on intraday time-scales. On the short time-scales, the BWB trend only shows up in ON 231, 3C 279, BL Lacertae, and 1E 1458.8 + 2249. There is a BWB trend in 3C 279 on the long time-scale. We estimate the upper limits of black hole mass for three blazars (i.e. ON 321, 1ES 1426 + 42.8, PKS 1510-089) using variability time-scales. On 2010 April 13, a potential quasi-periodic oscillation (QPO) with the period of P = 48.67 ± 13.90 min is found in 1ES 1426 + 42.8. The light curve on 2021 March 16 further shows the existence of the QPO phenomenon. The QPO in this target deserves further observation and confirmation.